Experimental study on thermal storage characteristics of cold storage distribution box. (1st November 2022) - Guo, Jiaming; Liu, Jing; Ren, Junjie; Zeng, Zhixiong; Lü, Enli
Abstract: Thermal storage characteristics are important evaluation indicators of cold storage equipment. A cold storage distribution box was tested to investigate the effects of the amount of phase change material (PCM), adjustment plate opening rate and the heat transfer area of the storage plate on the temperature elevating rate and temperature distribution in the box The effects of the above factors on the energy release characteristics were investigated by the variance analysis and the response surface methodology. The coupling of the heat transfer area of the storage plate and the amount of PCM had a significant effect on temperature elevating rate and temperature standard deviation. The results showed that the amount of PCM and the heat transfer area of the storage plate had a significant effect on the thermal storage characteristics. The heat transfer area of storage plate was changed from 0.09 m 2 to 0.11 m 2, adjustment plate opening rate was changed from 20 % to 40 %, and the amount of PCM was changed from 1.31 kg to 2.61 kg throughout the test. Temperature elevating rate increased and temperature standard deviation decreased as the value of one of three factors including the heat transfer area of storage, adjustment plate opening rate and the amount of PCM increased. The results of this research can provide a good reference for the design of cold chain facilities. Highlights: A cold storage distribution box based on liquid nitrogen injection was designed and developed. The AOP and HTA had a significant effect on temperature elevating rate and temperature standard deviation. The coupling of HTA and APOR had little effect on temperature elevating rate and temperature standard deviation. Temperature elevating rate increased while temperature standard deviation decreased as one of three factors increased.